The Predictive Ability of Dividend and Earnings Yields for Long-Term Stocks Returns - WU, Chunchi (Institutional Knowledge at Singapore Management University, 2000)
This study uses empirical models to examine the predictive ability of dividend and earnings yields for long-term stock returns. Results show that dividend and earnings yields share a similar predictive power for future stock returns and growth. It finds that the predictive power of dividend yields increases with the return horizon, but that yields forecast future returns and growth over a much longer horizon. Dividend and earnings yields exhibit high autocorrelation and strong contemporaneous relations.